Measurement of Isobaric Vapor-Liquid Equilibrium for Binary System β- Caryophyllene + Linalool and Eugenol + Linalool at 30 and 60 kPa - Masrur, Fachrizan Bilal; Heradiprakoso, Mauludandru; Tetrisyanda, Rizky; Kuswandi, Kuswandi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
The Vapor-Liquid Equilibrium experiment conducted for the final project focused on studying thermodynamic behavior of Eugenol, Beta-caryophyllene, and Linalool during their vapor and liquid phases. These compounds were chosen due to their significance in various industries, including pharmaceuticals, cosmetics, and flavorings. Equilibrium data between mixtures is still very limited in various conditions. The experiment tested on Othmer still that has been modified and validated corresponds to the vapor pressure data of each component using the equation of Antoine and Wagner-Ambrose obtained Average Absolute Deviation (AAD) T of 0,424% and 0,246%. This study aimed to obtain vapor-liquid equilibrium data for binary systems, which are Eugenol + Linalool and Beta-Caryophyllene + Linalool at 30 kPa and 60 kPa with a mole composition range (x1) from 0—1 for each pressure. Equilibrium data will be correlated with Wilson, Non Random Two-Liquid (NRTL), dan Portmanteau of Universal Quasichemical (UNIQUAC) model equations to represent all experiment data. The results of this study obtained the AAD values for each system β-Caryophyllene + Linalool and Eugenol + Linalool at a pressure of 30kPa and 60 kPa were below 0,5%